Academic Qualified Female Immigrants: Their Interrupted Careers, Identities Construction and Mental Health - All in the Name of a Love - Gláucia Queiroz (International Journal of Science, Technology and Society, 2026)
This article presents the results of scientific research conducted in Germany in 2024, which examines the integration experiences of Latin American women with academic qualifications and professional experience who migrated to Germany due to a marital relationship with a German resident. 205 respondents took part in the online survey, and 10 in-depth semi-structured interviews were conducted. The survey data were analysed statistically with support from the software SPSS. Triangulation techniques were used to compare and validate findings from both quantitative and qualitative data sources, enhancing the reliability of the results. The study aimed to identify patterns of associations between professional status, well-being and mental health, bicultural identity construction, and acculturative stress among immigrant women. The research focused on the mental health and well-being of these women, considering factors such as integration into the German labour market, the construction of identity/intercultural identity, and the role of motherhood in this process. In addition, the importance of motherhood in the lives of the respondents was investigated. The results indicated that, for this group, well-being and mental health are closely linked to the interruption of labour life and, in many cases, there is an impact on the individual’s identity. The most salient and worrying fact was the high number of female immigrants with clinical depression indications. The evidence highlights the need to pay greater attention to the well-being and mental health of professionally and academically qualified immigrant women. Such findings can strengthen debate around Germany and other European Union integration policies and practices for the development of strategies-political, economic, social and clinical-focused on the protection of mental health and the strengthening of the welfare of these populations.